Pengujian Kualitas Fungsional Website PERKASA Menggunakan Metode Black Box dengan Pendekatan Equivalence Partitioning - Vellisya Afifa Qonita; Indira Sistamarien; Siti Laila Nurjannah; Silvia Ariani Daulay; Gema Parasti Mindara; Aditya Wicaksono (TIN: Terapan Informatika Nusantara, 2025)
This study was conducted by applying Black Box testing using the Equivalence Partitioning method to validate the functionality of the PERKASA website, a digital consultation platform in the fisheries sector designed to support fish farmers. The research was carried out in a controlled testing environment with a focus on several main features, namely expert consultation, account login, account registration, articles, and user profile editing. The Equivalence Partitioning method was used to categorize inputs into classes representing valid and invalid conditions. Each test case was executed to determine whether the system produced outputs that matched the expected results. A quantitative approach was applied to compare the actual outcomes with the predefined expected values. Test results showed that out of 54 scenarios, 46 performed as expected, resulting in a functional validation rate of 85,19%. Meanwhile, several other scenarios showed discrepancies in specific input validation. Validation was performed on both client and server sides to ensure data integrity and an optimal user experience. These findings demonstrate that Equivalence Partitioning can serve as a useful method for supporting the development of new websites such as PERKASA, while also contributing to future research on web based information systems.